Experimental studies on the mechanical properties of garlic scape - Jing Yang; Baogang Xian; Shengben Lin; Xin Guo (PLoS ONE, 2026)
Garlic plants are composite materials with multi-scale structures, and the efficient separation of garlic scapes from pseudo-stems is the core challenge in the mechanized harvesting of garlic scape. To deeply elucidate the separation mechanism of garlic scapes and pseudo-stems, this study first confirmed the orthogonal anisotropy characteristics of garlic plants through microscopic morphology characterization. Based on the theory of composite material mechanics, a mechanical model of garlic plants was constructed. Tensile, compressive, and shear tests were conducted on intact garlic plants and their respective components (garlic scapes and pseudo-stems) using a universal testing machine, and key mechanical parameters were obtained systematically. Significant differences were identified between garlic scapes and pseudo-stems in terms of elastic modulus, peak strain, tensile strength, and shear strength through significance analysis, providing a mechanical basis for their selective separation. To verify the reliability of the experimental data, finite element simulation was performed to validate compression tests of garlic plants. The results indicated a high degree of agreement between the experimental and simulated curves, confirming the validity of the compressive tests. Furthermore, theoretical verification of the shear test results was carried out based on the mixing rule of composite materials, which revealed that the theoretical values of the plant elastic modulus were higher than the measured values in the tests. Combined with scanning electron microscopy (SEM) analysis, it was shown that this discrepancy primarily stemmed from the uneven slippage occurring inside the garlic scapes during the shearing process. This study systematically clarifies the differences in mechanical properties and the underlying separation mechanism between garlic scapes and pseudo-stems, providing critical parameters and theoretical foundations for the efficient and low-damage separation of garlic scapes from pseudo-stems in mechanized harvesting.